Phenotypic and antibiogram pattern of V. cholerae isolates from a tertiary care hospital in Mumbai during 2004–2013: a retrospective cross-sectional study. Issue 11 (25th November 2016) - Torane, V; Kuyare, S; Nataraj, G; Mehta, P; Dutta, S; Sarkar, B
Abstract : Objectives: Cholera is a major gastroenteric disease with reports on fluctuation and resistance. Hence, the objective is to determine the trend in seasonality, resistance pattern, prevalent biotypes, serotypes and phage types between 2004 and 2013 among Vibrio cholerae isolates. Design: A retrospective cross-sectional study. Settings: A single-centre study was carried out at a tertiary care hospital in a metropolitan city (Mumbai) of a developing country (India). Methods: Records of stool specimen cultures of patients with suspected cholera from January 2004 to December 2013 were analysed. The organisms were identified as per standard protocol. Antimicrobial susceptibility testing was performed as per Clinical Laboratory Standard Institute. Biotyping, serotyping and phage typing were carried out. From the confirmed cases of cholera, demographic and laboratory details were noted. Descriptive analysis was used and the data were presented in the form of percentages. Results: Vibrio cholerae was predominant in males and was isolated from 9.41% (439/4664) of stool specimens. Variability was found in terms of the gross appearance of stool specimens, seasonal trend and antibiotic resistance pattern. The antimicrobial susceptibility showed a waxing and waning pattern for most of the antibiotics (ampicillin, cefuroxime, chloramphenicol, tetracycline) tested, while for a few others the strains were either uniformly sensitive (gentamicin, norfloxacin) or resistant (trimethoprim-sulfamethoxazole, nalidixic acid). All isolates belonged to subgroup O1 and biotype El Tor. The most common serotype was Ogawa. The predominant phage type was T2 (old scheme) and T27 (new scheme). Conclusions: The predominant biotype, serotype and phage type were El Tor, Ogawa and T27 phage, respectively. The changing trends in antimicrobial resistance pattern over the years necessitate continued epidemiological and microbiological surveillance of the disease.